Heuristic evaluation on mobile halal detection application - Ahmad Hasan Ridwan; Irfan Safrudin; Muhammad Ali Ramdhani; Diena Rauda Ramdania (Institute of Advanced Engineering and Science, 2020)
As a country with the largest Muslim population in the world, the halal status of a food and beverage product is essential for the people of Indonesia. An application was created by the government to answer these concerns with the name